Agrobotanical Analysis of Bean (Phaseolus vulgaris L.) Equilibrium Populations Suitable for Regional Land Cultivation - Már, István; Juhász, Attila (Acta Agraria Debreceniensis, 2003)
The local bean landraces maintained at small-scale farming level should have importance as complementary source for completion of plant genetic resources with potential role in local land cultivation. Also, they should be used as primary material in breeding activities targeted on improving the foodstuffs quality. In the research were used especially landraces collected in Nyírség, Körös-mellék and Tápióvidék region. Our main objective was to reveal the relationship between the adaptation ability of landraces and the distance from their original collecting place. For that reason the location of the experimental plots was choosen by taking into account that they must be checked in each region, on it’s original region and similarly in other two different regions. On the base of the recorded agro-morphological traits we can get answers on the shaping of adaptation ability, and in the same time by a general chemical characterisation we should know more about the variation of qualitative parameters with a potential economical role. In the designing of experiment a main importance had the conditions where the research is taking place. All activities related to the maintenance of experiment were done in frame of a low input agricultural system to emphasize as much as possible the natural endowments of regeneration places.